Implementation of an Advance Care Planning Intervention in Nursing Homes: An International Multiple Case Study - Brazil, Kevin; Walshe, Catherine; Doherty, Julie; Harding, Andrew J E; Preston, Nancy; Bavelaar, Laura; Cornally, Nicola; Di Giulio, Paola; Gonella, Silvia; Hartigan, Irene; Henderson, Catherine; Kaasalainen, Sharon; et al. (The Gerontologist, 2024)
BACKGROUND AND OBJECTIVES: The inability of individuals in the advanced stage of dementia to communicate about preferences in care at the end-of-life poses a challenge for healthcare professionals and family carers. The proven effective Family Carer Decision Support intervention has been designed to inform family carers about end-of-life care options available to a person living with advanced dementia. The objectives of the mySupport study were to adapt the application of the intervention for use in different countries, assess impact on family satisfaction and decision-making, and identify costs and supportive conditions for the implementation of the intervention. RESEARCH DESIGN AND METHODS: A multiple-case study design was chosen where the nursing home was the case. Nursing homes were enrolled from six countries: Canada, Czech Republic, Italy, Netherlands, Republic of Ireland, and United Kingdom. RESULTS: Seventeen cases (nursing homes) participated, with a total of 296 interviews completed including family carers, nursing home staff, and health providers. Five themes relevant to the implementation of the intervention were identified: supportive relationships; committed staff; perceived value of the intervention; the influence of external factors on the nursing home; and resource impact of delivery. DISCUSSION AND IMPLICATIONS: There is a commonality of facilitators and barriers across countries when introducing practice innovation. A key learning point was the importance of implementation being accompanied by committed and supported nursing home leadership. The nursing home context is dynamic and multiple factors influence implementation at different points of time.
Keywords: senioři; Comfort care; Italy; Irsko; Advance Care Planning; demence; Nursing Homes; Canada; lidé; Česká republika; pečovatelské domovy; Netherlands; mužské pohlaví; Terminal Care; Spojené království; předběžné plánování péče; Czech Republic; Caregivers; rozhodování; Decision Making; Decision-making; ženské pohlaví; Humans; osoby pečující o pacienty; Dementia; péče o umírající; United Kingdom; Itálie; Family caregiver; Female; Aged; Ireland; Kanada; Male; Nizozemsko